Hungary under Soviet Rule II: A Survey of Developments from September 1957 to August 1958 - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): American Friends of the Captive Nations Chapters: Evidence of Continuing Soviet Intervention in Hungary; The Murder of Imre Nagy and Pál Maléter; Soviet Intervention in Hungary and Continuing Violation of Human Rights. Annexes: Resolutions adopted by UN General Assembly on Hungary; Report by Prince Wan; Communications from the Special Committee on the problem of Hungary to the Foreign Minister of the Hungarian People's Republic; Communiqué dated 21 June 1958 by the Special Committee on the problem of Hungary; Letters dated 26 June 1958 from the Special Committee on the problem of Hungary; Decree Law of 3 November 1957; Letter of 2 September 1957 from the Secretary General of the International Commission of Jurists; Partial List of Victims of terror in Hungary (Sept 1957 to August 1958).